2007
DOI: 10.1089/cpt.2007.9987
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report: Evaluation of Storage Conditions and Cryococktails during Peripheral Blood Mononuclear Cell Cryopreservation

Abstract: The use of cryopreserved peripheral blood mononuclear cells (PBMCs) has proven critical in both clinical and biomedical applications. While utilized, in numerous settings, the functionality of frozen PBMCs is often limited, and a disconnect exists between measured viability and outcome. In this study we investigated parameters affecting outcome including storage protocol, freeze media, and assessment assay. PBMCs were isolated from seven healthy donors and cryopreserved in: (1) a media-based cocktail (SAIC), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…These studies demonstrated that damage to the mitochondria resulted in release of caspases and ultimately, to the loss of the cell due to apoptosis. A similar outcome was observed by Cosentino and colleagues who demonstrated that improper storage (specifically, cycling of temperature in storage) resulted in higher levels of postthaw apoptosis for peripheral blood mononuclear cells (PBMNCs) stored on liquid nitrogen. Similarly, a study of UCB in long‐term storage suggests that HSCs expressing signs of apoptosis (annexin V staining) did not engraft when transplanted into an animal transplant model .…”
supporting
confidence: 74%
See 2 more Smart Citations
“…These studies demonstrated that damage to the mitochondria resulted in release of caspases and ultimately, to the loss of the cell due to apoptosis. A similar outcome was observed by Cosentino and colleagues who demonstrated that improper storage (specifically, cycling of temperature in storage) resulted in higher levels of postthaw apoptosis for peripheral blood mononuclear cells (PBMNCs) stored on liquid nitrogen. Similarly, a study of UCB in long‐term storage suggests that HSCs expressing signs of apoptosis (annexin V staining) did not engraft when transplanted into an animal transplant model .…”
supporting
confidence: 74%
“…Our hypothesis was that apoptosis could be used as a potential early marker for degradation of UCB units during long‐term storage. Cosentino and colleagues demonstrated improper temperature storage conditions resulted in increased apoptosis for PBMNCs and Shim and colleagues demonstrated that frozen and thawed CD34+ cells isolated from thawed UCB units expressing annexin V did not engraft in animals. To test whether apoptosis could be used as a biomarker for long‐term damage, UCB units were moved from liquid nitrogen to −80°C storage to impose a well‐characterized temperature lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media including Viaspan, CryoStor, Unisol, Adesta, Celsior and others, to name a few, when combined with CPAs for have been reported to improve cell survival to varying degrees. Improvements have been observed in systems including hepatocytes, 58,103 cord blood stem cells, 104 PBMCs, 67,105 fibroblasts, 11 keratinocytes, 69 blood vessels 101 and engineered tissues. 56 In these studies, evaluation of the cryopreservation media was conducted and correlated with improvements in cell survival, function and growth.…”
Section: Molecular-based Cell Death Associated With Cryopreservationmentioning
confidence: 99%
“…Numerous studies have now established that bioprocessing techniques are associated with the activation of molecular-based stress responses which contribute to cell loss during and following processing leading to failure[3,4,5,6,12,13,15,30,35]. These molecular responses can manifest as apoptosis or programmed cell death signaling.…”
Section: Introductionmentioning
confidence: 99%